MENGKRITISI PERAN BP4 DALAM MELESTARIKAN LEMBAGA PERKAWINAN - Zubaedi, Zubaedi (LP2M IAIN Mataram, 2010)
This study examines the roles and tasks of the Office of Marriage Counseling, Guidance and Preservation (BP4) in maintaining marriage in the globalization era. It is assumed that the Office is needed to give advice and counseling for the family to maintain its continuity. The study was carried out in Bengkulu and focused on the BP4â roles. The study reveals peopleâs perception of the BP4, its roles and achievement. Although the BP4 has already succeeded in mediating broken families and these families can be reconciled, its systematic and comprehensive ways in realizing all its roles still in many ways need improving. This study, therefore, offers some concepts and ideas that the Office needs to take into consideration if it wants to improve its role in the future.